2001
DOI: 10.1038/sj.cr.7290085
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a choline monooxygenase cDNA clone from Amaranthus tricolor and its expressions under stress conditions

Abstract: Plants synthesize the osmoprotectant glycine betaine (GB) via choline betaine aldehyde glycine betaine [1]. Two enzymes are involved in the pathway, choline monooxygenase (CMO) and betaine aldehyde dehydrogenase (BADH). A full length CMO cDNA (1,643bp) was cloned from Amaranthus tricolor. The open reading frame encoded a 442-amino acid polypeptide, which showed 69% identity with CMOs in Spinacia oleracea L. and Beta vulgaris L. DNA gel blot analysis indicated the presence of one copy of CMO gene in the A. tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
(49 reference statements)
3
18
1
Order By: Relevance
“…ABA plays a central role in the control of responses to stresses, such as salinity (Pons et al, 2013). However, our results and those of Meng et al (2001) indicate that transgenic plants overexpressing BADH exhibit enhanced tolerance to salt and drought treatments, but not to ABA. Furthermore, transgenic Arabidopsis exhibited enhanced tolerance during NaCl treatment in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…ABA plays a central role in the control of responses to stresses, such as salinity (Pons et al, 2013). However, our results and those of Meng et al (2001) indicate that transgenic plants overexpressing BADH exhibit enhanced tolerance to salt and drought treatments, but not to ABA. Furthermore, transgenic Arabidopsis exhibited enhanced tolerance during NaCl treatment in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…This is supported by our finding that the plant species in which one of the two isoenzymes is a high-BAL-affinity enzyme according to our criterion of possessing Ala or Cys in the position of Ala-441 of SoBADH, as well as other plants in which there have been found so far only one isoenzyme with Ala in this position, such as spinach and sugar beet (Beta vulgaris), or with Cys, such as wheat (Triticum aestivum), have been reported as being GB accumulators, whereas those plants that only have low-BAL-affinity isoenzymes are reported as lacking the ability to accumulate GB (Supplemental Table S3). Moreover, a functional CMO has only been found in species of Amaranthaceae that have the high-BAL-affinity isoenzyme, such as amaranth Meng et al, 2001), orache (Atriplex hortensis; Shen et al, 2002), spinach , and sugar beet , whereas a nonfunctional gene was found in rice (Luo et al, 2007) and the recombinant CMO protein from Arabidopsis has no activity (Hibino et al, 2002). There are other CMO sequences deposited in GenBank, but it is not yet known whether the CMO proteins in these plants are functional or not.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated molecular weights of 42.67 kDa and 42.54 kDa for monomers of AnCMO and AsCMO, respectively, are close to the experimentally determined values for other plants, e.g., spinach (42.8 kDa; Rathinasabapathi et al 1997), Amaranthus tricolor (>43 kDa; Meng et al 2001). However, the instability index of 40 or above predicts a protein to be unstable (Gasteiger et al 2005), hence these CMOs may not be monomeric.…”
Section: Discussionmentioning
confidence: 55%